Video-assisted pericardioscopy. How to improve diagnostic efficacy in pericardial effusions - Pêgo-Fernandes,Paulo M. (2001)
OBJECTIVE: To assess, in a prospective way, the experience with video-assisted pericardioscopy obtained in patients with pericardial effusion of unclear etiology in the preoperative period. METHODS: From January 1998 to June 2000, 20 patients were operated upon with the aid of video-assisted pericardioscopy. On echocardiography, 17 of these patients had significant pericardial effusion, and 3 had moderate pericardial effusion. Video-assisted pericardioscopy was performed through a small incision of the Marfan type. RESULTS: The diagnosis of pericardial effusion was established as follows: idiopathic in 9 (45%) patients, neoplastic in 4 (20%), resulting from hypothyroidism in 3 (15%), tuberculous in 2 (10%), due to cholesterol in 1 (5%), and chylopericardial in 1 (5%). The biopsy was positive in 30% of the patients, and the etiology could not be defined in 45% of the patients. CONCLUSION: Video-assisted pericardioscopy proved to be a method with low morbidity and a high index of diagnostic positivity. A high percentage of pericardial effusions are caused by viral infections, which are not diagnosed through current methods, being, therefore, classified as idiopathic.